Soil Interaction and Grout Behavior for the NREL Reference Monopile Offshore Wind Turbine - Mário Vieira; Miguel Viana; Elsa Henriques; Luís Reis (Journal of Marine Science and Engineering, 2020)
Monopiles for offshore wind are the most used foundations by farm operators due to their low production costs, when compared to other bottom-fixed or floating foundations. In this research, a monopile foundation for offshore wind power was evaluated for its soil interaction and grout behavior, and an appropriate numerical model for the structural analysis of the foundation and tower was developed. FAST 8, an aero-hydro-servo-elastic numerical code developed by NREL, was used to obtain the loads applied on the supporting structures. These loads were pre-processed before they were inputted on the finite element model, developed using the finite element software ANSYS. The considered conical grout connection, which connects the monopile to the transition piece through friction, was modeled under a changing-status nonlinearity condition. To model the soil–pile interaction, a p-y model was applied using the ANSYS APDL commands. Static, modal, and transient structural analyses were produced to study the structure suitability for its use on offshore environments. Different soil interactions were modeled, and their results were then compared within the transient and modal analysis, indicating that the angle of the grout connection strongly affects the loading conditions on the grout. Moreover, scouring affects the dynamic behavior of the overall supporting structures, thus protection against this phenomenon is suggested.